ADVANCING DIGITAL INNOVATION TO STRENGTHEN BRAND VALUE: SUPPORTING WOODEN CRAFT ENTREPRENEURS’ CREATIVE DEVELOPMENT FOR WIDER MARKET APPEAL - Gopal Meena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study explores the relationship between innovation and brand equity, focusing on how strategic orientation and digitalization influence brand development, especially in the handicraft industry. The research integrates key theories, including the Technology-Organization-Environment (T-O-E) framework, contingency theory, and resource-based value (RBV), to examine how these dimensions shape innovation typologies and contribute to brand equity. It posits that a firm’s ability to assimilate digital innovations—particularly in technology-driven environments—significantly impacts its brand equity. However, it cautions that merely adopting digital strategies without consistent strategic orientation and managerial resolve may not guarantee innovation success. The study also highlights specific challenges within the handicraft sector, using Saharanpur’s wooden craft industry as a case study. Findings suggest that fostering innovation in clustered regions can enhance competitiveness more effectively than in dispersed firms, echoing Porter’s cluster theory. Additionally, the research offers practical insights for managers and policymakers to support sustainable innovation by balancing exploitative and exploratory practices. Overall, the study underscores that strategic orientation, combined with digitalization and managerial commitment, is critical for embedding innovation in organizational culture and enhancing brand equity.